Nematode biodiversity in south-western Nigerian watermelon cropping systems, with reference to Meloidogyne and its management - Bello, T.T. (North-West University, 2020)
Watermelon is increasingly produced and consumed in Nigeria and sub-Saharan Africa (SSA). However, limited information exists regarding the nematode fauna associated with the crop. Therefore, the overall aim of this study was to determine the nematode assemblages associated with watermelon, to investigate the reproduction potential of populations of the predominant plant-parasitic nematodes identified and to assess the host status of commercially available cultivars in south-west Nigeria to the predominant nematode pest species. Of the 30 free-living nematode genera identified from soil samples, Cephalobus, followed by Rhabiditis, Aphelenchus and Aporcelaimus, were predominant. Variation in nematode community structures across the 50 fields was apparent for mean maturity indices, metabolic footprints, feeding-type composition and coloniser-persister (c-p) structure. Faunal analyses characterised 52% of the fields as having stable and enriched soil food webs, which is beneficial for crop production. A new species, Aporcelaimellus nigeriensis sp. n., was furthermore identified and described from this study. Of the 12 plant-parasitic nematode species identified, Meloidogyne spp. were predominant, followed by Helicotylenchus dihystera, Pratylenchus zeae and Scutellonema bradys. Applying morphological and molecular techniques, four Meloidogyne spp. were identified from the sampling sites. Meloidogyne enterolobii was the most prevalent, followed by M. incognita, M. javanica and M. arenaria. Meloidogyne arenaria is reported for the first time from south-west Nigerian cropping systems. Significant associations were observed between the frequency of occurrence of the predominant nematode pest genera/species and soil properties as well as rainfall. The reproduction potential of 25 Meloidogyne spp. populations (containing single-species) and/or communities (containing mixed-species) obtained from watermelon fields were determined under glasshouse conditions, while the host response of six commercially available watermelon cultivars to the three predominant root-knot nematode species (M. incognita, M. javanica and M. enterolobii) were also done. For both studies an initial and repeat experiments were conducted over 56 days. For the reproduction potential experiments, ±5 000 eggs and second-stage juveniles (J2) of each of the 25 Meloidogyne populations and/or communities were inoculated on roots of two-leaf stage seedlings of the root-knot nematode susceptible tomato (Lycopersicon esculentum Mill.) cultivar Tropimech. For the host status experiments, roots of six commercially available watermelon cultivars were inoculated with ±5 000 eggs and J2 of in-vivo reared, single-species populations of M. incognita, M. javanica and M. enterolobii. The reproduction potential of the Meloidogyne spp. communities and the host response of the cultivars were assessed based on the i) number of egg masses, ii) final nematode population (Pf) and iii) reproduction factor (Rf) per root system. No significant interaction existed between the initial and repeat experiments of the reproduction potential experiments, while a significant interaction was apparent between the two host status experiments. However, for the reproduction potential experiments higher Pf and Rf values were recorded for most of the cultivars for the initial compared to the repeat experiment. The highest Rf was obtained for a mixed community of M. enterolobii and M. javanica (L 15), while the lowest Rf was ascribed to a mixed species community (L16) containing M. arenaria and M. enterolobii. Host status assessments of cultivars showed that all cultivars evaluated were susceptible (Rf >1) to the three species of Meloidogyne, although substantial variation among the cultivars’ host responses to the three Meloidogyne spp. existed. For example, cultivar Koloss F1 supported the lowest population densities for M. enterolobii (Pf = 40 002; Rf = 6.1); Sugar Dragon for M. javanica (Pf = 12 947; Rf = 2.6); and M. incognita (Pf = 10 670; Rf = 2.1); the highest population densities were maintained in roots of cultivar Charleston Gray for M. enterolobii (Pf = 73 522 ; Rf = 14.7); Erato F1 for M. javanica (Pf = 47 684 ; Rf = 9.5); and Charleston Gray for M. incognita (Pf = 63 395; Rf = 12.7). All Pf and Rf values recorded across the treatments were significantly lower than those of the susceptible tomato standard check. This study provides novel information regarding i) the free-living and ii) plant-parasitic nematodes associated with watermelon from SSA; iii) a new Aporcelaimellus sp. report; and baseline information on iv) the reproduction potential of Meloidogyne spp. populaitons and communities occurring in south-west Nigeria; as well as the v) the host status of commercially available watermelon cultivars grown across south-west Nigerian agro-ecological systems to single-species Meloidogyne populuations. The data generated from this study hence represent valuable and useful information to watermelon growers and can contribute towards sustainable cultivation of the crop in Nigeria.